Report of the Working Group on Flood Management for the Ninth Five Year Plan (1997-2002) - Planning Commission (Planning Commission, 1996)
To carry out a state-wise as well as of Central Sector review of the performance in terms of objectives of physical and financial targets under Flood Control, Drainage and anti-sea erosion programme including non-structural measures during the Eighth Plan so as to identify bottlenecks and deficiencies in implementation for deciding corrective measures if any. Also, the Group will study the mismatch, if any between the priorities indicated in the comprehensive plans of flood control prepared by the concerned State/GFCC/Brahmaputra Board and actual execution, with broad indication of causes and likely remedies for the same.
Government of India Ministry of Water Resources Central Water Commission
Government of India Ministry of Water Resources Central Water Commission